VALIDITY OF GUIDED INQUIRY-BASED WORKSHEETS ON VIII-GRADE SUBSTANCE PRESSURE MATERIALS (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
Abstract: The lack of use of teaching materials in the form of worksheets which can facilitate class VIII-A students Bahrul Ulum Middle School, who quickly understood science concepts through hands-on practice, made learning science boring. So it is necessary to develop worksheet guided inquiry-based learning models on substance pressure materials, which emphasize discovering concepts through direct practice with intensive teacher guidance. This study aims to describe (1) The process of developing guided inquiry-based worksheets on substance pressure materials, and (2) The product resulting from the developing worksheets after a valid, practical, and effective process. The development model used is ADDIE, with five stages: analysis, design, development, implementation, and evaluation. The results showed (1) The process of developing worksheets is based on the stages of the ADDIE development procedure, and (2) The products resulting from the developing worksheets obtain a validity score of 95% with "Very Valid" criteria, a practical score based on the observation sheet 94% with "Very Practical" criteria and student response questionnaire of 96,5% with "Very Practical" criteria, and an effectiveness score of 93,3% with "Very Effective" criteria. The developing worksheets are suitable for use as teaching material for students in learning science.